The Improvement of Oil Palm Seedling through Shade, Manure and Organic Liquid Fertilizer in Ultisol Media - Muhimmatul Husna; Umi Salamah; Welly Herman; Winalia Agwil (PLANTA TROPIKA, 2023)
The development of oil palm nurseries in Bengkulu is constrained by plant media, such as ultisol soil, which has low nutrients. Nutrients in ultisol can be equipped by organic matters such as manure and liquid organic fertilizer (LOF). Moreover, the light intensity also could affect seeds growth. This research aimed to determine the improvement of oil palm in pre-nursery as affected by LOF, types of manure application, and shade to obtain the best treatment combination. The research was conducted from June until September 2021 in Beringin Raya, Bengkulu city. The study was arranged in a split-plot design in a completely randomized block design consisting of 3 factors with three replications. The main plot was shade percentage ((N1=50% dan N2=75%), the subplot was liquid organic fertilizer doses ((B1=0%, B2=5% and B3=10%), the sub subplot was the types of manure (P1=cow manure, P2=chicken manure, P3=goat manure, and P4= without manure). The observation was made on the growth components of oil palm seedlings until 3.5 months. There was an interaction between shade, LOF, and types of manure to the number of leaves. There was no interaction between LOF and types of manure. The shade did not affect the growth factors of the seeds. Applying 10% LOF can improve the growth of oil palm seedlings. Chicken manure has the highest variable value on the hump diameter and the number of leaves seedlings.